2013
DOI: 10.1016/j.jval.2013.08.226
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy Among HIV-Infected Patients Attending to a University Infectious Diseases Clinic in Venezuela

Abstract: Patient's characteristics, drug utilization patterns and resource utilization were analyzed. Results: Data were available for a sample of 244 eligible patients. The average age of the study population was 24.3 years (SD= 12.5). While the maximum medication possession ratio (MPR) for alternate month administration is 50%, patients on TIP had an average MPR of 52.8%, while patients on TIS and OTF had an average MPR of 41.4% and 39.7%, respectively. Treatment persistence at 3 months was estimated at 85.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In studies conducted in Venezuela, the research on HIV-adherence patients has focused on analyzing some psychological, interpersonal, or biological factors (13)(14)(15), but in none of them, the personality factor has been considered explicitly. This study was aimed at determining the direct and indirect effects of the personality factor, motives and behavioral competencies on adherence behaviors in a sample of highly HIVadherent patients from Venezuela, based on the psychological model presented using structural equation modeling.…”
Section: Factors and Self-administered Instrumentsmentioning
confidence: 99%
“…In studies conducted in Venezuela, the research on HIV-adherence patients has focused on analyzing some psychological, interpersonal, or biological factors (13)(14)(15), but in none of them, the personality factor has been considered explicitly. This study was aimed at determining the direct and indirect effects of the personality factor, motives and behavioral competencies on adherence behaviors in a sample of highly HIVadherent patients from Venezuela, based on the psychological model presented using structural equation modeling.…”
Section: Factors and Self-administered Instrumentsmentioning
confidence: 99%
“…Despite convergent body of evidence has confirmed the role of individual factors on medication-adherence behaviors in Latin America countries and the Caribbean region, such as Argentina [7], Chile [8], Peru [9] and the Dominican Republic [10], little progress has been made in countries like Venezuela. In fact, only two studies using HIV+ samples have been found, in both cases putting emphasis in the influence of socio-demographic and clinical patient's characteristics on medication-adherence behaviors [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite convergent body of evidence has confirmed the role of individual factors on medication-adherence behaviors in Latin America countries and the Caribbean region, such as Argentina [7], Chile [8], Peru [9] and the Dominican Republic [10], little progress has been made in countries like Venezuela. In fact, only two studies using HIV+ samples have been found, in both cases putting emphasis in the influence of socio-demographic and clinical patient's characteristics on medication-adherence behaviors [11,12].Considering those antecedents and the need to investigate the influence of individual factors on medication-adherence behaviors in Venezuelan HIV+ persons, this study was justified in a psychological model for the research of adherence behaviors (PMAB) in persons living with chronic diseases, including HIV infection [13]. As show in Figure 1, the model emphasizes the interaction of psychological and biological variables along four phases.…”
mentioning
confidence: 99%